Phenomenon of Demikhov. In the 1st Moscow Medical Institute named after Sechenov (1956–1960). V.P. Demikhov's third business trip to Germany (September 1959). Advances of world transplantation (1951–1959). "The Soviet suturing machine", or "Androsov's stapler" (1959) - S. P. Glyantsev (Трансплантология (Москва))
Phenomenon of Demikhov. In the 1st Moscow Medical Institute named after Sechenov (1956–1960). V.P. Demikhov's third business trip to Germany (September 1959). Advances of world transplantation (1951–1959). "The Soviet suturing machine", or "Androsov's stapler" (1959).